CHINESE VEGETABLE GARDEN FARMERS RESPONSE ON AGRICULTURAL EXTENSION OF VEGETABLE COMMODITIES IN PANTAI CERMIN DISTRICT SERDANG BEDAGAI, NORTH SUMATERA PROVINCE - Cherly M. Butar-Butar; Tience E. Pakpahan; Arie Hapsani (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The Indonesian consists of various ethnic and cultural groups both native, one of them is Chinese. Most of their professions are traders. In the area of Pantai Cermin District, Serdang Bedagai Regency, North Sumatra Province, there are still many Chinese etnics who live and work as farmers. They are called Chinese Vegetable farmers. The purpose of research was to determine percentage of response Chinese Vegetable farmers in agricultural extension and to determine the factors influencing the response of Chinese Vegetable farmers in extension of vegetable agricultural commodities in Pantai Cermin District, Regency Serdang Bedagai. This research method is quantitative descriptive analysis, with variables: knowledge, experience, learning needs, cultural values, innovation attributes, communication channels, and socio-cultural environment. Based on the response rate of Chinese farmers for level of production and income is high category. Where the value of farmers 'responses to production levels is 69.52%, while the value of the components of farmers' responses to income levels is 71.54%. Overall the response rate of Chinese farmers is high, which is 70.53%. The significant factor influences the response of Chinese farmers in the expansion of vegetable gardens on the vegetable commodity farm at Pantai Cermin is the variable of cultural value.